2020
DOI: 10.1038/s41598-020-65082-1
|View full text |Cite
|
Sign up to set email alerts
|

Profound alterations of the chromatin architecture at chromosome 11p15.5 in cells from Beckwith-Wiedemann and Silver-Russell syndromes patients

Abstract: Beckwith-Wiedemann syndrome (BWS) and Silver-Russell syndrome (SRS) are imprinting-related disorders associated with genetic/epigenetic alterations of the 11p15.5 region, which harbours two clusters of imprinted genes (IGs). 11p15.5 IGs are regulated by the methylation status of imprinting control regions ICR1 and ICR2. 3D chromatin structure is thought to play a pivotal role in gene expression control; however, chromatin architecture models are still poorly defined in most cases, particularly for IGs. Our stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(30 citation statements)
references
References 49 publications
(66 reference statements)
1
29
0
Order By: Relevance
“…The presence of MLID supports, indeed, the hypothesis of imprinting gene networks involved in the cross-talk among imprinted loci, probably mediated by complex chromatin structures and ncRNAs [ 39 , 40 ]. This hypothesis is also supported by recent evidence in BWS patients on the loss of the chromatin structure of the IGF2/H19 and CDKN1C/KCNQ1OT1 domains, which disrupts the fine-tuned control of gene expression in the two clusters [ 41 ]. The chromatin architecture of these domains differs between the maternal and paternal allele, and these allele-specific structures are required for the correct expression of the imprinted genes within these domains.…”
Section: Genetic and Epigenetic Alterations In Bwssupporting
confidence: 58%
See 1 more Smart Citation
“…The presence of MLID supports, indeed, the hypothesis of imprinting gene networks involved in the cross-talk among imprinted loci, probably mediated by complex chromatin structures and ncRNAs [ 39 , 40 ]. This hypothesis is also supported by recent evidence in BWS patients on the loss of the chromatin structure of the IGF2/H19 and CDKN1C/KCNQ1OT1 domains, which disrupts the fine-tuned control of gene expression in the two clusters [ 41 ]. The chromatin architecture of these domains differs between the maternal and paternal allele, and these allele-specific structures are required for the correct expression of the imprinted genes within these domains.…”
Section: Genetic and Epigenetic Alterations In Bwssupporting
confidence: 58%
“…In healthy cells, the IGF2/H19 and CDKN1C/KCNQ1OT1 domains fold in complex chromatin conformations that facilitate the control of imprinted loci mediated by distant enhancers. In BWS cells, the profound alterations of such chromatin architectures lead to the loss of the cross-talk between the two domains and the impairment of the correct expression of imprinted genes [ 41 ].…”
Section: Genetic and Epigenetic Alterations In Bwsmentioning
confidence: 99%
“…Here, CTCF binds the unmethylated paternal copy of the ICR, which also comprises the promoter that drives Kcnq1ot1 expression on this parental chromosome [ 105 ]. The allelic CTCF binding mediates specific long-range interactions on the paternal chromosome, detected by 3C-based technology, that correlate with the allelic expression of several genes within the domain [ 75 , 102 , 106 ]. Another locus that shows both allelic CTCF binding and allelic lncRNA expression is the imprinted Zdbf2 domain [ 107 ].…”
Section: Emerging Roles Of Imprinted Lncrnas In Chromatin Architecturementioning
confidence: 99%
“…Recently, Rovina et al. ( 50 ) reported an interaction between IC1 and IC2 in a limited number of patient lymphoblastoid cell lines. To determine whether we observed such an interaction in our patient fibroblast lines, we expanded the window of interactions.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, a study by Rovina et al. demonstrated that interaction between the DMR and the KCNQ1 intron 2 CTCF sites is significantly reduced in BWS patient cell lines ( 50 ). Together, these results suggest that CTCF performs an important function in organizing the imprinted locus and may precede initial deposition of DNA methylation or play a role in maintaining DNA methylation.…”
Section: Introductionmentioning
confidence: 99%